Blockchain implementation and the management of intellectual property rights: A Systematic review. - Urquiaga Júarez, Evelyn Marcia; Torrealva Mariños, Gabriela Del Pilar; Flores Idrugo, Eddier Albino; Ramos Flores, Elizabeth Liliana (LACCEI, 2025)
Currently, the protection of digital works is a great challenge, since it is easy to copy or use them without permission, affecting the rights of creators. Blockchain technology has emerged as a possible solution, since it allows recording information securely, transparently and without the possibility of alteration. In this study, the PRISMA and PICO methodology is used, which facilitated the search for scientific studies of great relevance with the help of its standardized steps for this research; in addition, the LIA Method was applied for the synthesis of the articles included, simplifying the writing of the results, providing greater transparency and reliability in the information written. Therefore, the results were divided into two parts: thematic and bibliometric results, in the bibliometric section figures are presented with respect to the main characteristics of the articles that have been included in the review (year, affiliation, country of publication, database), on the other hand, in the thematic aspect the application tools used as support for the blockchain and the effects found in each of the most relevant scientific productions in the current research carried out were highlighted.